2020
DOI: 10.1101/2020.02.20.955161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel cortical-brainstem pathways to attentional analgesia

Abstract: 13Pain perception is diminished when attention is diverted. Our previous human fMRI study, using a 14 2x2 factorial design with thermal stimuli and concurrent visual attention task, linked the brainstem 15 triad of locus coeruleus (LC), rostroventromedial medulla (RVM) and periaqueductal grey (PAG) to 16 attentional analgesia. This study was repeated with a larger cohort, replicating our earlier findings. 17 Pain intensity was encoded by the RVM, whilst activity in the contralateral LC correlated with the 18 m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(55 citation statements)
references
References 108 publications
(107 reference statements)
11
40
4
Order By: Relevance
“…The PAG is a key node in the DPMS but also an important orchestrator of autonomic and sensorimotor systems that is engaged to support mPFC function in aversive learning, emotional modulation and pain modulation which are all relevant to the chronic pain phenotype (Keay and Bandler, 2001;Franklin et al, 2017;Rozeske et al, 2018;Huang et al, 2019). In humans, changes in functional connectivity between the mPFC/ACC, and the PAG are commonly observed in experimental paradigms that produce emotional, attentional and placebo/nocebo influences on pain as well following delivery of analgesic drugs and often interpreted as reflecting engagement of the DPMS (Wager et al, 2004;Wiech et al, 2014;Wanigasekera et al, 2018;Oliva et al, 2020). Moreover, changes in the functional connectivity between regions of the mPFC and the PAG are often correlated with changes in pain perception and/or disease progression, (Cifre et al, 2012;Hemington and Coulombe, 2015;Harper et al, 2018;Segerdahl et al, 2018;Wanigasekera et al, 2018;González-Roldán et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The PAG is a key node in the DPMS but also an important orchestrator of autonomic and sensorimotor systems that is engaged to support mPFC function in aversive learning, emotional modulation and pain modulation which are all relevant to the chronic pain phenotype (Keay and Bandler, 2001;Franklin et al, 2017;Rozeske et al, 2018;Huang et al, 2019). In humans, changes in functional connectivity between the mPFC/ACC, and the PAG are commonly observed in experimental paradigms that produce emotional, attentional and placebo/nocebo influences on pain as well following delivery of analgesic drugs and often interpreted as reflecting engagement of the DPMS (Wager et al, 2004;Wiech et al, 2014;Wanigasekera et al, 2018;Oliva et al, 2020). Moreover, changes in the functional connectivity between regions of the mPFC and the PAG are often correlated with changes in pain perception and/or disease progression, (Cifre et al, 2012;Hemington and Coulombe, 2015;Harper et al, 2018;Segerdahl et al, 2018;Wanigasekera et al, 2018;González-Roldán et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 39 subjects (mean age 23.7, range [18 -45] years, 18 females) completed the fMRI imaging sessions with a 2*2 factorial experimental design (RSVP task easy / hard and high / low thermal stimulus) with a different drug administered orally before each session (naltrexone (50mg), reboxetine (4mg) or placebo, Figure 1). The behavioural signature of attentional analgesia is a task*temperature interaction, driven by a reduction in pain ratings during the high temperature-hard task condition (Brooks et al, 2017;Oliva et al, 2021;Oliva et al, 2020). A first level analysis of the pooled pain data across all experimental sessions showed: a main effect of temperature (F (1,38) = 221, P=0.0001) with higher scores under the high temperature condition; a main effect of task (F (1,38) = 4.9, P=0.03); and importantly demonstrated the expected task*temperature interaction consistent with attentional pain modulation (F (1, 38) = 10.5, P = 0.0025, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that two parallel pathways are implicated in driving brainstem activity related to attentional analgesia (Brooks et al, 2017;Oliva et al, 2020). Projections from rostral anterior cingulate cortex (rACC) were found to drive the periaqueductal grey (PAG) and rostral ventromedial medulla (RVM), which animal studies have shown to work in concert using opioidergic mechanisms to regulate spinal nociception (Fields, 2004;Fields and Basbaum, 1978;Heinricher et al, 1994;Ossipov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations